Perencanaan Pengembangan Embung Melalui Destination Branding Sebagai Penunjang Potensi Daya Tarik Wisata di Desa Sumberagung, Kec. Gondang, Kab. Nganjuk - Ramadhani Aura Kinanthi; Annisa Rahadianti; Nadila Ayu Citra Armana; Andhika Wira Putra Dharma (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
This study aims to analyze and plan destination branding by KKNT university students and local communities in Sumberagung Village to develop the Sumberagung reservoir. The condition of tourism, which continues to experience an increase in the number of tourists, encourages university students to continue to plan to optimize the existing potential tourism in Sumberagung Village, one of which is in the branding field. It is necessary to improve the quality of human resources related to the understanding of development, especially in digital marketing, so that the community can accept the optimization of the information transformation process. This study used a complete participation data collection method and in-depth interviews with a descriptive type and a qualitative approach. The result of implementing this community service is the creation of branding for Embung Sumberagung, with the entity logo, tagline, and tourism map. This study is expected to serve as a guide or reference in maximizing the existing tourism potential in Sumberagung Village through destination branding.